The disintegrating conscience and the decline of modernity - Smith, Steven D. 1974- (University of Notre Dame Press, 2023)
In The disintegrating conscience and the decline of modernity, Smith takes as his starting point Jacques Barzun's provocative assertion that "the modern era" is coming to an end. Smith considers the question of decline by focusing on a single theme--conscience--that has been central to much of what has happened in Western politics, law, and religion of the past half-millennium
Keywords: Geschichte; Gewissen; Religion; Rechtsprechung; Westliche Welt; Conscience / History; Conscience, Examination of / History; Conscience (Morale) / Histoire; Examen de conscience / Histoire